2016
DOI: 10.5812/jjm.16241
|View full text |Cite
|
Sign up to set email alerts
|

Single Chain Antibodies Against gp55 of Human Cytomegalovirus (HCMV) for Prophylaxis and Treatment of HCMV Infections

Abstract: Background:Immunotherapy is a promising prospective new treatment for cytomegalovirus (CMV) infections. Neutralizing effects have been reported using monoclonal antibodies. Recombinant single chain antibodies (scFvs) due to their advantages over monoclonal antibodies are potential alternatives and provide valuable clinical agents.Objectives:The aim of this study was to select specific single chain antibodies against gp55 of CMV and to evaluate their neutralizing effects. In the present study, we selected speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The importance of viral clearance has led to the development of strategies, including passive immunization and cytokine therapy (34)(35)(36)(37). In persistent viral infections, such as HBV infection, cytokine therapy is suggested as a useful immunotherapy (38).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of viral clearance has led to the development of strategies, including passive immunization and cytokine therapy (34)(35)(36)(37). In persistent viral infections, such as HBV infection, cytokine therapy is suggested as a useful immunotherapy (38).…”
Section: Discussionmentioning
confidence: 99%
“…For all the clones, the 950 bp band (VH-linker-VL) was obtained ( Figure 5). Two Prevailing fingerprinting patterns were detected, ie, Pattern 1 (Lanes 1, 4,6,7,8,10,11,13,15,17,20), scFv1 with frequency of 55% and pattern 2 (lanes 2, 3, 5, 9, 12, 14, 16, 18, 19), scFv2 with frequency of 45%. One clone from each pattern was selected to use in further investigations.…”
Section: Pcr and Dna Fingerprintingmentioning
confidence: 99%
“…The obtained antibody, named scFv, can be selected against a proper epitope and the mono-specific scFvs can be isolated (14)(15)(16)(17)(18)(19). They can be a good alternative to the common therapeutic drugs in human disease therapy because of their unique properties like human origin, high connection and better tissue penetration, low molecular weight, and high physical and chemical stability (20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Single chain antibodies, which are composed of VH-Linker-VL, are small antigen binding units with unique properties, including human origin, not eliciting HAMA reaction (human anti-mouse antibody response), high specificity, affinity properties, deep penetration in solid tissues, easy manipulation, and economic cost production in prokaryotes (15)(16)(17)(18)(19). Recent studies have shown the important role of these antibodies in cancer immunotherapy (20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%